Expression of Pinopodes in the Endometrium from Recurrent Pregnancy Loss Women. Role of Thrombomodulin and Ezrin - D’Ippolito, Silvia (J Clin Med, 2020)
Background: Pinopode expression has been suggested as a marker of endometrial receptivity. Methods: We set up an experimental study comparing endometrial tissue from recurrent pregnancy loss (RPL, n = 30) and fertile control (CTR, n = 20) women in terms of pinopode expression/morphology; expression of thrombomodulin (TM) and ezrin; cytoskeletal organization. Endometrial samples were collected during implantation window and evaluated by scanning electron microscopy, western blot, and immunofluorescence. Results: We found that RPL endometrial tissue showed: (i) increased pinopodes density (* p < 0.05); (ii) a reduced diameter of pinopodes (* p < 0.05); (iii) a decreased TM and ezrin expression (p < 0.05). Additionally, confocal images showed a significantly reduced expression of phosphorylated (p)-ezrin, confirming the results obtained through immunoblot analysis. Immunofluorescence staining showed that in CTR samples, junctions between cells are intact and clearly visible, whereas actin filaments appear completely lost in RPL endometrial samples; this suggests that, due to the impaired expression and activity of TM and ezrin, actin does not bind to plasma membrane in order to orchestrate the cytoskeletal actin filaments. Conclusions: Our findings suggest that an impaired expression of TM and expression/activation of ezrin may affect the connection between the TM and actin cytoskeleton, impairing the organization of cytoskeleton and, eventually, the adequate pinopode development.